Longer Work/Rest Intervals During High-Intensity Interval Training (HIIT) Lead to Elevated Levels of miR-222 and miR-29c - Schmitz, Boris; Rolfes, Florian; Schelleckes, Katrin; Mewes, Mirja; Thorwesten, Lothar; Krüger, Michael; Klose, Andreas; Brand, Stefan-Martin (Frontiers in Physiology, 2018)
Aim: MicroRNA-222 (miR-222) and miR-29c have been identified as important modulators of cardiac growth and may protect against pathological cardiac remodeling. miR-222 and -29c may thus serve as functional biomarkers for exercise-induced cardiac adaptations. This investigation compared the effect of two workload-matched high-intensity interval training (HIIT) protocols with different recovery periods on miR-222 and -29c levels. Methods: Fifty-three moderately trained females and males (22.0±1.7 years) fulfilled the eligibility criteria and were randomized into two HIIT groups using sex and exercise capacity. During a controlled 4-week intervention (two sessions/week) a 4x30 HIIT group performed 4x30 s runs (all-out, 30 s active recovery) and a 8x15 HIIT group performed 8x15 s runs (all-out, 15 s active recovery). miR-222 and -29c as well as transforming growth factor-beta1 (TGF-beta1) mRNA levels were determined during high-intensity running as well as aerobic exercise using capillary blood from earlobes. Performance parameters were assessed using an incremental continuous running test (ICRT) protocol with blood lactate diagnostic and heart rate (HR) monitoring to determine HR recovery and power output at individual anaerobic threshold (IAT). Results: At baseline, acute exercise miR-222 and -29c levels were increased only in the 4x30 HIIT group (both p<0.01, pre- vs post-exercise). After the intervention, acute exercise miR-222 levels were still increased in the 4x30 HIIT group (p<0.01, pre- vs post-exercise) while in the 8x15 HIIT group again no acute effect was observed. However, both HIIT interventions resulted in elevated resting miR-222 and -29c levels (all p<0.001, pre- vs post-intervention). Neither of the two miRNAs were elevated at any ICRT speed level at baseline nor follow-up. While HR recovery was improved by >24% in both HIIT groups (both p≤0.0002) speed at IAT was improved by 3.6% only in the 4x30 HIIT group (p<0.0132). Correlation analysis suggested an association between both miRNAs and TGF-beta1 mRNA (all p≤0.006, r≥0.74) as well as change in speed at IAT and change in miR-222 levels (p=0.024, r=0.46). Conclusions: HIIT can induce increased circulating levels of cardiac growth-associated miR-222 and -29c. miR-222 and miR-29c could be useful markers to monitor HIIT response in general and to identify optimal work/rest combinations.